Academic Trust Betrayed: Unravelling the Factors Behind Lecturers’ Vulnerability to Social Engineering Attacks (American Journal of Education and Technology, 2025)
Social engineering (SE) attacks are the most treacherous cyber-attacks, which are not rooted in the manipulation of code or exploitation of system vulnerabilities but target the human factor, which has historically been the weakest link in the security chain. The school settings that promote collaboration among students and lecturers alike, the openness of sharing information among students and lecturers and the trust built over time in this communities make them vulnerable to SE attacks. This study then seeks to investigate how effective cybersecurity education and training intervention has in reducing the susceptibility of SE attacks among the staff of higher education. 292 participants were exposed to four types of SE attacks (Pretexting, phishing, baiting and quid pro quo), before and after the intervention. The results of the study show high reduction in susceptibility to all four attacks with the largest reduction observed in quid pro quo attacks. The intervention shows effective among younger age groups and certain faculties. Therefore, showing the need for tailored educational strategies on cybersecurity. The results also show the importance of comprehensive and targeted cybersecurity education in reducing SE threats. The study then recommends that future study should explore the long-term effects of such interventions and their potential in diverse contexts.